Phytochemical and Toxicity Evaluation of Traditional Herb: Lagerstroemia speciosa L. (Banaba) by MCF-7 Cell Line and Brine Shrimp Lethality Bioassay (Bangladesh Pharmaceutical Journal, 2019)
The main objective of this study was to determine the cytotoxicity of crude extract of the leaves of Lagerstroemia speciosa (Banaba). In vitro MCF-7 cell line and in vivo brine shrimp lethality bioassay methods were followed to investigate the cytotoxicity of the selected sample. In this study, the qualitative phytochemical assessment demonstrated the presence of alkaloids, carbohydrate, glycosides, saponins, terpenes, steroids, phenols and flavonoids in Banaba extract. Moreover, the present findings revealed the non-cytotoxic nature of L. speciosa leaves extract on both MTT-assay and brine shrimp lethality bioassay.Bangladesh Pharmaceutical Journal 22(1): 45-49, 2019